Development of a technology for the preparation of a dry nutrient medium for anthrax vaccine production - D. A. Sharov; A. A. Leshchenko; E. A. Kovalenko; D. V. Borovskoy; V. V. Krupin; S. V. Bagin; D. A. Mokhov; A. G. Lazykin; I. V. Kosenkov; A. N. Moshkov (Биопрепараты: Профилактика, диагностика, лечение)
Currently, submerged cultivation of the Bacillus anthracis STI-1 strain for live anthrax vaccine production requires liquid nutrient media, which have disadvantages of a short shelf life (no more than one month) and a narrow range of storage temperatures (2–8 °С). Dry media, in contrast, have a number of indisputable advantages: such media are transportable and easy to use, have a standard capability to retain properties, and can be stored without preservatives at 2–30 °С for 2–5 years. The aim of this work was to develop a technology for the preparation of a dry nutrient medium for anthrax vaccine production. Materials and methods: The study used the Bacillus anthracis STI-1 vaccine strain and a nutrient medium for its cultivation, containing a 70:30 mixture of an enzymatic digest of casein and a pre-processed corn extract solution. Drying of the nutrient medium was carried out on a spray-drying unit. The authors evaluated physicochemical parameters of experimental medium batches. The shelf life was determined by an accelerated stability study. The dry nutrient medium was used to produce a live anthrax vaccine. Quality attributes of the vaccine were assessed for compliance with regulatory requirements. Results: The authors developed the dry media production technology. According to it, the liquid nutrient medium is fed to the drying unit at a rate of 20–25 dm3/h. The spray air pressure is 0.02 MPa. Temperatures at the drying chamber inlet and outlet are 118–122 °С and 85–90 °С, respectively. The technology was used to obtain 3 experimental batches of the dry medium. The study results demonstrate that the technology is reproducible, and the tested quality attributes of experimental medium batches are consistent with the requirements. According to the accelerated stability study, the shelf life of the dry nutrient medium at 2–30 °С is at least 3 years. Experiments demonstrated the possibility of using the dry nutrient medium for live anthrax vaccine production. Critical quality attributes of the vaccine obtained with the medium met regulatory requirements. Conclusions: The developed technology allows for the production of a standard dry nutrient medium with a prolonged shelf life, which is convenient for live anthrax vaccine production.